Emotions Towards Satisfaction and Complaint Behavior Using Perceived Quality: A Hedonic Approach - Tara Aldiera Prijono (Business Education Program of Universitas Pendidikan Indonesia, 2022)
More attention should be paid to the emotional side of the service experience. This is because customer satisfaction is highly dependent on how services are delivered and may affect future service delivery. In this context, it is assumed that emotions will affect customer dissatisfaction behavior and pleasure service satisfaction differently according to the perceived quality as a parameter. In this study, a quantitative data collection method was adopted by distributing questionnaires to 268 respondents. Research shows that different types of dissatisfaction and customer satisfaction can lead to different outcomes due to perceived quality effects. This research shows perceived quality has a significant impact on behavioral outcomes for hedonic services, especially positive emotions, compared to negative emotions. Future research is expected to dig more relation between emotion and other regulatory variables to provide a different perspective.